Analysis of the prophylactic effect of thymosin drugs on COVID‐19 for 435 medical staff: A hospital‐based retrospective study. Issue 3 (8th October 2020) - Liu, Xiulan; Liu, Yi; Wang, Liuming; Hu, Luhong; Liu, Dong; Li, Juan
Abstract: To explore the role of thymosin drugs in the prevention of novel coronavirus disease (COVID‐19), we analyzed the preventive effects of different medication timings on health medical staff, and then provided recommendations for pharmaceutical monitoring of thymus drugs. The hospital‐based retrospective study analyzed 435 medical staffers, treated with or without thymosin drugs as preventive medicines in our hospital of Wuhan City, from January 25 to March 25, 2020. For the prophylactics, the medical staff was prevented from pre‐exposure prophylaxis (risk prevention of exposure to COVID‐19 patients before using thymosin drugs) and postexposure prophylaxis (risk prevention of exposure to COVID‐19 patients after using thymosin drugs). The effectiveness and safety of thymosin drugs were studied in the prevention and control of COVID‐19 application, in real‐world data research for the application of the drug for COVID‐ 19. In a similar exposure environment, compared to medical staffers who did not take preventive medicine, the use of thymosin drugs, before exposure and after exposure had an insignificant effect, and the adverse drug reaction (ADR) was increased, especially when thymosin drugs were used together with α‐interferon.